2021
DOI: 10.1002/oby.23133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Energy Turnover on the Regulation of Energy and Macronutrient Balance

Abstract: Energy turnover, defined as the average daily total metabolic rate, can be normalized for basal metabolic rate in order to compare physical activity level between individuals, whereas normalization of energy turnover for energy intake (energy flux) allows investigation of its impact on regulation of energy partitioning independent of energy balance. Appetite sensations better correspond to energy requirements at a high compared with a low energy turnover. Adaptation of energy intake to habitual energy turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
0
8
0
1
Order By: Relevance
“…Increasing energy expenditure through exercise may be more effective in improving short-term appetite control than energetic restriction alone, often considered the main target in the management of obesity. As recently reviewed by Bosy-Westphal et al (15) , unlike exercise, small increase in energy flux induced by short sleep duration or increased mental work can lead to an increase in energy intake and thus to a deregulation of the energy balance. Future studies comparing different levels of energy flux over a longer time frame are needed to better understand and characterise the appetitive responses to energy balance manipulations that may inform design of interventions that improve sustainable weight loss interventions and fight the childhood obesity pandemic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increasing energy expenditure through exercise may be more effective in improving short-term appetite control than energetic restriction alone, often considered the main target in the management of obesity. As recently reviewed by Bosy-Westphal et al (15) , unlike exercise, small increase in energy flux induced by short sleep duration or increased mental work can lead to an increase in energy intake and thus to a deregulation of the energy balance. Future studies comparing different levels of energy flux over a longer time frame are needed to better understand and characterise the appetitive responses to energy balance manipulations that may inform design of interventions that improve sustainable weight loss interventions and fight the childhood obesity pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…deficit, maintenance or surplus of energy). Thus, a high-energy flux (HEF) is determined by a high level of EI where the level of energy expenditure is also high (15) . In healthy adults, Hägele et al showed that HEF was associated with lower subsequent ad libitum intake, an increase in Glucagon-like peptide-1 (GLP-1) concentrations and a decrease in acylated ghrelin, insulin concentrations, hunger and desire to eat (14) .…”
mentioning
confidence: 99%
“…Although the etiology of acquired obesity is often contested [ 1 ], there is strong evidence dating from the mid-20th century that reductions in PA, high physical inactivity (PI), and excessive sedentary behavior (SB) are strong determinants of this phenotype in both human and non-human animals [ 1 , 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. To summarize briefly, first, PA is the major modifiable determinant of caloric consumption [ 27 , 28 , 31 , 34 , 35 , 36 , 37 ]. Second, when individuals reduce their PA, their consumption declines more slowly than their caloric expenditure [ 27 , 28 , 31 , 34 , 35 , 36 ].…”
Section: Acquired Obesity: Its Etiology and Response To Interventionmentioning
confidence: 99%
“…To summarize briefly, first, PA is the major modifiable determinant of caloric consumption [ 27 , 28 , 31 , 34 , 35 , 36 , 37 ]. Second, when individuals reduce their PA, their consumption declines more slowly than their caloric expenditure [ 27 , 28 , 31 , 34 , 35 , 36 ]. This leads to relative hyperphagia (overconsumption) and positive energy balance—with individuals consuming more calories than they expend.…”
Section: Acquired Obesity: Its Etiology and Response To Interventionmentioning
confidence: 99%
See 1 more Smart Citation